Towards a method for monitoring the coupling evolution of microservice-based architectures - Apolinário, Daniel Rodrigo de Freitas; França, Breno Bernard Nicolau de (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2020)
The microservice architecture is claimed to satisfy ongoing software development demands, such as resilience, flexibility, and velocity. However, developing applications based on microservices also brings some drawbacks, such as the increased software operational complexity. Recent studies have also pointed out the lack of methods to prevent problems related to the maintainability of these solutions. Disregarding established design principles during the software evolution may lead to the so-called architectural erosion, which can end up in a condition of unfeasible maintenance. As microservices can be considered a new architecture style, there are few initiatives to monitoring the evolution of software microservice-based architectures. In this paper, we introduce the SYMBIOTE method for monitoring the coupling evolution of microservice-based systems. More specifically, this method collects coupling metrics during runtime (staging or production environments) and monitors them throughout software evolution. The longitudinal analysis of the collected measures allows detecting an upward trend in coupling metrics that could be signs of architectural erosion. To develop the proposed method, we performed an experimental analysis of the coupling metrics behavior using artificially-generated data.